Population and poverty in Ireland on the eve of the Great Famine - Alan Fernihough; Cormac Ó Gráda (Queen's University Centre for Economic History (QUCEH), 2018)
The link between demographic pressure and economic conditions in pre-Famine Ireland has long interested economists. This paper re-visits the topic, harnessing the highly disaggregated parish-level data from the 1841 Census of Ireland. Using population per value adjusted acre as a measure of population pressure, our results indicate that on the eve of the Great Famine of 184650, population pressure was positively associated with both illiteracy rates and the prevalence of poor quality housing. But while our analysis shows that population pressure was one of the primary factors underpinning pre-Famine poverty, it also highlights the importance of geography and human agency. A counterfactual computation indicates that had Ireland's population stayed at its 1800 level, this would have led to only modest improvements in literacy and housing.
Keywords: N33; B30; J11; 330; Famine; Malthus; Population; Ireland